Fission yeast Sop2p: a novel and evolutionarily conserved protein that interacts with Arp3p and modulates profilin function. - Balasubramanian, M K (1996)
Profilins bind to monomeric actin and also interact with ligands such as phosphoinositide 4,5-bisphosphate, the proline-rich protein VASP and a complex of four to six polypeptides identified in Acanthamoeba that includes two actin-related proteins. Here, we report the identification and characterization of an essential gene from Schizosaccharomyces pombe, sop2+, a mutation in which rescues the temperature-sensitive lethality of a profilin mutation, cdc3-124. The sop2-1 mutant is defective for cell elongation and septation, suggesting that it is involved in multiple cortical actin-requiring processes. Consistent with a role in actin cytoskeletal function, negative interactions have been identified between sop2-1 and act1-48, a mutant allele of actin. Sop2p is a novel 377 amino acid polypeptide with similarity to proteins of the beta-transducin repeat family. Sop2p-related proteins have been identified by sequencing projects in diverse species, and we have isolated a human cDNA highly related to sop2+, SOP2 Hs, which functionally complements the sop2-1 mutation. Sop2p proteins from all species contain peptide sequences identical or highly similar to two peptide sequences from an Acanthamoeba beta-transducin repeat protein present in the profilin binding complex. Biochemical analyses demonstrate that Sop2p is present in a complex which also contains the actin-related protein, Arp3p. Immunofluorescence studies reveal the presence of Sop2p in (i) punctate structures distributed throughout the cell, (ii) cables that extend the length of the cell, and (iii) a medial band in a small percentage of septating cells. Collectively these data demonstrate the interaction of Sop2p with Arp3p, profilin and actin.